Powder injection moulding of stainless steels reinforced with nano size alumina particles - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2009)
This study compares the effect of Al2O3 nano-particle additions on the densification and mechanical properties response of injection molded 316L stainless steels. The sintered density of straight as well as Al2O3 reinforced injection molded 316L stainless steels increases with the increase in sintering time. The addition of Al2O3 additions improves the hardness with increasing sintering time. Sintered samples were examined by SEM and optical microscopy.